Polarization sensitive optical coherence tomography with single input for imaging depth-resolved collagen organizations - Peijun Tang (Nature Publishing Group, 2021)
Discrete differential geometry-based polarization tracing method enables PSOCT imaging of depth-resolved collagen organizations.